Fostering Environmental Awareness in Elementary Students Through the 'CILUKBA' Science Learning Program - Wulandari, Tri; Nisa, Ana Fitrotun; Masjid, Akbar Al; Cahyani, Berliana Heru (FKIP Universitas Lampung, 2024)
Current educational developments require integration between academic learning and student character formation. One of the characteristics related to global issues is love of the environment, which can be instilled from an early age through a practical activity-based approach. The CILUKBA (Environmental Love Makes Us Happy) program is an initiative to teach the values of environmental love through science learning. This research aims to evaluate the success of the